(untitled) (Research, Society and Development, 2021)
The present study aims to evaluate the influence of the stages of lactation (colostrum, transition and mature) on the composition of the main fatty acids and sums of fatty acids in human milk from lactating women with full-term infants. For this, approximately 5 ml of human milk was collected individually, in the same period of the day, and after 1 hour of the breast being emptied, through manual milking, then the fatty acid composition was performed by means of chromatography in gas phase coupled to flame ionization detector (CG-DIC). The fatty acid found mostly for colostrum was linoleic acid (18:2n-6), whereas for transition and mature milk it was oleic acid (18:1n-9), in addition to all essential fatty acids and strictly essential were identified and quantified in the three phases. It was possible to observe that the lactation stage directly influences the fatty acid composition, with colostrum milk being the one with the greatest distinction between the lactation phases, and transitional milk and mature milk having more similarity to each other.